Effects of habitat fragmentation on plant reproductive success and population viability at the landscape and habitat scale - Newman, B.; Ladd, P.; Brundrett, M.; Dixon, Kingsley (2013)
Habitat fragmentation can significantly affect plant reproductive success and ultimately population viability, but little is known about the magnitude, direction or time scale of these impacts on plant-pollinator mutualisms. In this study, four species of terrestrial orchid with specialist and generalist pollination syndromes were used to investigate the effects of fragmentation on capsule set in urban bushland remnants. Supplementary pollination showed pollination limitation, but not resource limitation, occurs across all species. Habitat and landscape scale fragmentation predictor variables were used to build parsimonious models that explained capsule set data collected over 2 years. We found the sexually deceptive species, Caladenia arenicola, to be sensitive to interactions between landscape (perimeter to area ratio) and habitat scale (bare ground cover and population size) predictor variables. The effect of perimeter to area ratio was heavily tempered by the significant negative influence of bare ground cover, where values of over 40% bare ground cover resulted in reproductive failure. We found that generalist pollinated species had significant interactions at the habitat scale including significant positive interactions between capsule set and population size and litter cover. Our results suggest the effects of habitat fragmentation at the landscape and habitat scale are important drivers of population viability. Our results suggest population viability will depend on the sensitivity of the pollination syndrome and the pollinator involved. This study highlights the need for research into reproductive success across multiple spatial scales to improve and inform conservation efforts.